Tindak Pidana Perjudian Dalam Tinjauan Hukum Pidana (Studi Kasus Putusan Nomor 491/Pid.B/PN Mdn Tahun 2017) - Rio Pambudi; Aulia Rosa Nasution; Muazzul Muazzul (JUNCTO: Jurnal Ilmiah Hukum, 2020)
Gambling is basically a game where there are parties who bet each other to choose one choice among several choices where only one choice is correct and being a winner means that the player who loses the bet will give the bet to the winner. Gambling rules and bets are determined and agreed before the match starts. Talking about "Gambling" which is forbidden by religion, is also expressly prohibited by positive law. This can be seen from the provisions of article 303 of the Criminal Code, Jo. Law No.7 of 1974 concerning Control of Gambling Jo. PP.No. 1981 Jo. Presidential Instruction and Minister of Home Affairs Instruction No.5, April 1, 1981. The type of research used in writing this thesis is to use normative legal research methods. Normative legal research is research that studies the study of documents, namely using various secondary data such as statutory regulations laws, court decisions, legal theories, and can be in the form of opinions of scholars. As for efforts to prevent gambling so that it can be overcome, it is desirable for religious leaders and law enforcers to often conduct socialization such as lectures at places of worship so that they are aware that gambling is prohibited in any form.